Modeling the hydrological impact of land use change in a dolomite-dominated karst system - Bittner, Daniel; Narany, Tahoora Sheikhy; Kohl, Bernhard; Disse, Markus; Chiogna, Gabriele (Journal of Hydrology, 2018)
Hydrological models represent valuable tools to investigate the impacts of land use changes on water resources. Most commonly, distributed, physically-based models are applied for land use change impact studies in hydrology. However, providing a physically-based and detailed description of subsurface flows in karst systems is challenging. Lumped models, in contrast, are easy to implement and widely used in karst hydrological research, albeit not applicable for land use change impact studies. To overcome these limitations, we developed a new semi-distributed model LuKARS (Land use change modeling in KARSt systems) that lumps the predominant hydrotopes (i.e. distinct landscape units characterized by homogeneous hydrological properties as a result of similar land use and soil types) present in a catchment as independent, non-linear units. Flows from each hydrotope represent a specific response of the vadose zone (soil-epikarst-infiltration zone) in a defined recharge area. The saturated zone consists of a single linear storage unit recharged by each hydrotope independently. The main goal of this approach was to investigate land use change impacts in a dolomite karst system exploited for the water supply of the city of Waidhofen a.d. Ybbs (Austria) by changing the area covered by each hydrotope. Here, land use changes occured in the form of increasing spaces used for dolomite mining and at the expense of existing forest sites. With our parametrized model, we were able to reproduce the measured discharge in the largest spring of the Waidhofen karst system (Kerschbaum spring). Moreover, we succeeded in transferring the parametrized hydrotopes to other recharge areas (Hinterlug and Mitterlug) and validated the transferability of the modeling approach. Finally, we successfully showed the model's applicability for land use change impact studies by validating the calibrated model in a period in which the space of the dolomite quarries in the Kerschbaum recharge area almost doubled. The results of our study show that an increase of the dolomite quarries negatively affects the water supply of the city of Waidhofen a.d. Ybbs.
CRIS-Team Scopus Importer:2024-04-17
Keywords: Hydrotope; Karst aquifer; Karst modeling; Land use change; Rainfall-discharge model